A Novel Variant of the CHD2 Gene Associated With Developmental Delay and Myoclonic Epilepsy - Zhu, Lina; Peng, Fujun; Deng, Zengwen; Feng, Zhichun; Ma, Xiuwei (Frontiers in Genetics, 2022)
Pathogenic variants in CHD2 have been reported to have a wide range of phenotypic variability in neurodevelopmental disorders, such as early-onset epileptic encephalopathy, developmental delay, and behavior problems. So far, there is no clear correlation between genotypes and phenotypes. This study reports a Chinese patient with a novel heterozygous CHD2 mutation (c.4318C>T, pArg1440*). Her main clinical manifestations include developmental delay, myoclonic epilepsy, and hypothyroidism. Then, we reviewed a total of 144 individuals carrying CHD2 variants with epileptic encephalopathy. In terms of clinical manifestations, these patients are usually described with variable epilepsy phenotypes, including idiopathic photosensitive occipital epilepsy, Dravet syndrome, Jeavons syndrome, Lennox–Gastaut syndrome, juvenile myoclonic epilepsy, and non-specific epileptic encephalopathy. Among them, myoclonic seizures and generalized tonic-clonic seizures are the main seizure types in all patients hosting CHD2 single-nucleotide or indel variants (non-CNVs). At the molecular level, there are 102 types of CHD2 non-CNVs in 126 patients, almost one mutational type corresponding to one person, and there is no difference in the incidence ratio of each position. Furthermore, we summarized that a small proportion of patients inherited CHD2 variants, and not all patients with CHD2 variants had seizures. Importantly, the phenotypes, especially seizures control and fever sensitivity, and genotypes had a relative association. These results enriched the database of CHD2-relative neurodevelopmental disorders and provided a theoretical foundation for researching the relationship between genotypes and phenotypes.